Human ADMC-Derived Adipocyte Thermogenic Capacity Is Regulated by IL-4 Receptor - Fernando Lizcano; Diana Vargas; Ángela Gómez; Astrid Torrado (Stem Cells International)
Type two innate immune system is anti-inflammatory and may play an important role as the means whereby “browning” is induced in subcutaneous adipocytes. It was shown that IL-4 may influence the fate of adipose cell precursors by promoting differentiation towards more thermogenic adipocytes in mice. Here, we investigated the influence of IL-4 and IL-4 receptor, a type two immune cytokine pathway, on the metabolic activity and thermogenic potential of human adipocytes differentiated from adipose-derived mesenchymal stem cells (ADMSCs) obtained from subcutaneous samples of healthy women undergoing abdominoplasty. Western blot analysis, qPCR, and biochemical analyses were performed 10 days after ADMSC differentiation into mature adipocytes was induced. IL-4 receptor was expressed in both precursor and differentiated adipocytes, and IL-4 treatment increased phosphorylation Y641 of signal transducer and activator of transcription 6 (STAT6) in both cell types. IL-4 treatment also increased expression of thermogenic proteins PGC-1α, UCP-1, and CITED1. In addition, IL-4 increased the secretion of adiponectin, leptin, and FGF21 and promoted lipolysis in differentiated adipocytes. In conclusion, IL-4 may directly modulate differentiation of human adipocytes towards a beige phenotype acting through IL-4 receptors on both adipose precursors and differentiated human adipocytes, metabolic effect that must be considered in some antiallergic drugs.